Adhesive, adhesive for laminating optical members or window films, adhesive sheet, and method for producing adhesive sheet

A cross-linked adhesive using plant-derived dimer acids and dimer diol with a carbodiimide compound addresses compatibility issues, ensuring low haze and durability for bonding optical members and window films.

JP7619000B2Active Publication Date: 2025-01-22MITSUBISHI CHEM CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2020178375
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-10-23
Publication Date
2025-01-22
Estimated Expiration
2040-10-23

AI Technical Summary

Technical Problem

Existing adhesives using polyester resin for bonding optical members and window films suffer from poor compatibility between dimer acid and carbodiimide group-containing compounds, leading to increased haze and coloration, as well as low modulus of elasticity, resulting in appearance abnormalities and inadequate durability under high temperature and humidity conditions.

Method used

A cross-linked adhesive composition containing a polyester resin derived from plant-based dimer acids and dimer diol, combined with a carbodiimide group-containing compound, optimized to achieve low haze and excellent adhesion, durability, and transparency.

Benefits of technology

The adhesive composition maintains transparency and durability under high temperature and humidity, with improved adhesion to various substrates, suitable for bonding optical components and window films, while being environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007619000000001
    Figure 0007619000000001
  • Figure 0007619000000002
    Figure 0007619000000002
  • Figure 0007619000000003
    Figure 0007619000000003
Patent Text Reader

Abstract

To provide an adhesive excellent in haze, and excellent also in durability and adherence under high temperature and high humidity even if it is an adhesive using a material derived from plants friendly to global environment.SOLUTION: The adhesive is obtained by crosslinking a polyester-based resin (A) having a polyvalent carboxylic acids (a1)-derived structural moiety, and a polyol (a2)-derived structural moiety with an adhesive composition [I] containing a carbodiimide group-containing organic compound (B), where the polyester-based resin (A) is a polyester-based resin having a structural moiety derived from at least any one of dimer acids, and a dimer diol, and when making an adhesive layer with a sickness of 50 μm using the adhesive, the haze of the adhesive layer is 5% or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polyester-based pressure-sensitive adhesive, in particular a pressure-sensitive adhesive for bonding optical members or window films, a pressure-sensitive adhesive sheet, and a method for producing a pressure-sensitive adhesive sheet, and more specifically to a pressure-sensitive adhesive that uses environmentally friendly plant-derived raw materials, which has good adhesion to various adherends such as metals and glass, excellent durability under high temperature and high humidity conditions, and further has excellent dent resistance and can maintain transparency even when a hydrolysis inhibitor is added, a pressure-sensitive adhesive for bonding optical members or window films, a pressure-sensitive adhesive sheet, and a method for producing a pressure-sensitive adhesive sheet. [Background technology]

[0002] In recent years, pressure sensitive adhesives have come to be used for bonding parts, etc., in order to reduce the size and weight of products. As such pressure sensitive adhesives, pressure sensitive adhesives that use polyester resins and have excellent adhesive strength have been investigated. Since polyester resins are generally susceptible to hydrolysis, it has been investigated to incorporate a hydrolysis inhibitor into the polyester resin to inhibit hydrolysis of the polyester resin and thereby improve durability. Furthermore, one application for adhesives using polyester resins that has been widely considered is as adhesives for attaching window films to the window glass of automobiles, buildings, etc. for the purposes of blocking ultraviolet rays in sunlight, preventing the attraction of flying insects, protecting privacy, preventing crime, preventing glass from shattering, decoration, etc. Furthermore, in the case of adhesives for bonding optical components, the gap between the image display panel of a liquid crystal display or organic EL display and the protective panel or touch panel member placed on the front side (viewing side) of the image display panel is filled with adhesive to suppress reflection of incident light and outgoing light from the displayed image at the air layer interface.

[0003] These pressure sensitive adhesives for attaching window films or optical components may be required to have a greater adhesive thickness than usual from the viewpoint of shock absorption.

[0004] Meanwhile, in recent years, as part of measures to combat the depletion of fossil fuel resources and global warming, the use of plant-derived raw materials, which are renewable resources, has been recommended, and there is a demand for adhesives with a high degree of bioplasticity that use plant-derived raw materials that are environmentally friendly.

[0005] Under these circumstances, for example, Patent Document 1 proposes a polyester-based adhesive composition containing a polyester, a hydrolysis stabilizer, a tackifier, and a crosslinking agent, and using a specific tackifier, as an adhesive using a polyester resin. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2015-134906 A Summary of the Invention [Problem to be solved by the invention]

[0007] However, in the technology disclosed in Patent Document 1, the compatibility between the polyester resin obtained by using dimer acid and dimer diol and the carbodiimide group-containing compound is poor, so the haze increases significantly, and further, since a tackifier is blended, there is a concern about coloring due to the tackifier. Furthermore, even if the tackifier is removed from the technology disclosed in Patent Document 1, the haze becomes very high, so when used as an adhesive for bonding highly transparent members such as optical members and window films, the appearance is poor and it is practically unusable. Furthermore, in the technology disclosed in Patent Document 1, the resin is too soft, so when made into an adhesive sheet, the elastic modulus is too low, making it prone to dents, and when made into a transparent adhesive sheet, the dents tend to cause abnormalities in appearance, and the resin is still not satisfactory as an adhesive for bonding optical components, window films, etc., and further improvements are required.

[0008] Under these circumstances, the present invention aims to provide an adhesive that uses environmentally friendly plant-derived raw materials and yet has excellent transparency and durability and adhesive strength under high temperature and high humidity conditions, in particular an adhesive for bonding optical components or window films, and an adhesive sheet. [Means for solving the problem]

[0009] However, the present inventors have discovered that when an environmentally friendly polyester resin using at least one plant-derived raw material such as dimer acids or dimer diols is used in an adhesive obtained by curing an adhesive composition containing a polyester resin, by using a carbodiimide group-containing compound in combination to reduce haze, it is possible to obtain an adhesive that is environmentally friendly, has good adhesive strength to various adherends, and is also excellent in durability and transparency under high temperature and high humidity conditions, particularly an adhesive that is effective for laminating optical members or window films, and have completed the present invention.

[0010] That is, a first gist of the present invention is an adhesive obtained by crosslinking an adhesive composition [I] containing a polyester-based resin (A) having a structural moiety derived from a polyvalent carboxylic acid (a1) and a structural moiety derived from a polyol (a2), and a carbodiimide group-containing compound (B), wherein the polyester-based resin (A) is a polyester-based resin containing a structural moiety derived from at least one of a dimer acid and a dimer diol, and when the adhesive is used to form an adhesive layer having a thickness of 50 μm, the haze of the adhesive layer is 5% or less.

[0011] Furthermore, in the present invention, a second aspect is an adhesive for laminating optical members or window films comprising the adhesive, a third aspect is an adhesive sheet having an adhesive layer containing the adhesive of the first aspect or the adhesive of the second aspect, and a fourth aspect is a method for producing the adhesive sheet of the third aspect.

[0012] Typically, plant-derived resins tend to have inferior appearances compared to petroleum-derived resins due to the presence of trace impurities, etc., due to the fact that they are plant-derived. Therefore, there is a problem in that a high proportion of plant-derived raw material monomers is used (bioplastic degree) although it is kind to the global environment, it has a poor appearance. In addition, when a polyester-based adhesive containing a structural portion derived from dimer acids or dimer diol is used to increase the degree of bioplasticity, the polyester-based resin has a long alkyl chain in the main chain and side chain, so when it is used in combination with a highly polar carbodiimide group-containing compound, the difference in their properties causes them to not be completely compatible, resulting in poor appearance. Furthermore, if the thickness of the adhesive is increased with consideration for shock absorption, etc., this leads to a further increase in haze, so in adhesives where appearance is important, the combination of a polyester-based adhesive containing a structural portion derived from dimer acids or dimer diol with a carbodiimide group-containing compound was greatly hesitated.

[0013] Furthermore, polyester-based adhesives with many long alkyl chains tend to be flexible, leading to poor dent resistance and poor appearance. For these reasons, when a polyester-based resin using dimer acids or dimer diols is blended with a carbodiimide group-containing compound to produce an adhesive with a high bioplasticity, it is very difficult to improve the moist heat resistance, appearance performance, and other requirements while maintaining a high bioplasticity. In the present invention, it has been found that the object of the present invention can be achieved by adjusting the content of the structural portion of the polyester-based resin (A) and optimizing the type of the carbodiimide group-containing compound (B) while still producing an environmentally friendly polyester-based resin. Effect of the Invention

[0014] The adhesive of the present invention is an adhesive obtained by crosslinking an adhesive composition [I] containing a polyester resin (A) having a structural portion derived from a polyvalent carboxylic acid (a1) and a structural portion derived from a polyol (a2) and a carbodiimide group-containing compound (B), the polyester resin (A) being a polyester resin containing a structural portion derived from at least one of dimer acids and dimer diol, and the haze of the adhesive layer when the adhesive is used to form an adhesive layer having a thickness of 50 μm is 5% or less. Therefore, the adhesive is environmentally friendly, while having good adhesion to various adherends and excellent durability and transparency under high temperature and high humidity. Therefore, the pressure-sensitive adhesive of the present invention can be effectively used as a single-sided or double-sided pressure-sensitive adhesive sheet for use in bonding optical components, a single-sided or double-sided pressure-sensitive adhesive sheet for fixing components of portable electronic devices, a single-sided or double-sided pressure-sensitive adhesive sheet for fixing electronic components, and an adhesive for bonding window films. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] The configuration of the present invention will be described in detail below, but these are merely examples of preferred embodiments. In the present invention, the term "type" of carboxylic acids and the like includes not only acids such as carboxylic acids, but also derivatives of carboxylic acids and the like, such as salts of carboxylic acids, anhydrides of carboxylic acids, halides of carboxylic acids, and esters of carboxylic acids.

[0016] The pressure-sensitive adhesive of the present invention is a crosslinked pressure-sensitive adhesive composition [I] containing a polyester resin (A) and a carbodiimide group-containing compound (B). The components constituting the pressure-sensitive adhesive of the present invention will be described below in order.

[0017] <Polyester resin (A)> The polyester-based resin (A) used in the present invention is a polyester-based resin having structural moieties derived from polyvalent carboxylic acids (a1) and polyol (a2), and containing at least one of a structural moiety derived from dimer acids and a structural moiety derived from dimer diol, and preferably contains a structural moiety derived from dimer acids as the structural moiety derived from polyvalent carboxylic acids (a1). Such a polyester-based resin (A) is usually obtained by copolymerizing a copolymerization component containing a polyvalent carboxylic acid (a1) and a polyol (a2). In the present invention, the polyester-based resin (A) can be produced by using a dimer acid as the polyvalent carboxylic acid (a1) and / or a dimer diol as the polyol (a2) for the above-mentioned copolymerization components.

[0018] The structural portion derived from the polyvalent carboxylic acids (a1) accounts for 20 to 97% by weight, preferably 30 to 96% by weight, and particularly preferably 40 to 95% by weight of the entire polyester resin (A). The structural portion derived from the polyol (a2) occupies 3 to 70% by weight, preferably 5 to 60% by weight, and particularly preferably 8 to 50% by weight of the entire polyester resin (A).

[0019] The content of the structural portion derived from at least one of dimer acids and dimer diols in the polyester resin (A) is preferably 50% by weight or more, more preferably 55 to 95% by weight, even more preferably 60 to 90% by weight, and particularly preferably 70 to 85% by weight, based on the polyester resin (A). If the content is too low, the resin tends to become too hard and the adhesive strength tends to decrease. If the content is too high, the resin tends to become too soft and the adhesive properties tend to decrease slightly.

[0020] [Structural moiety derived from polyvalent carboxylic acids (a1)] The structural portion derived from the polyvalent carboxylic acids (a1) preferably contains a structural portion derived from a dimer acid. The content of the structural portion derived from the dimer acid in the structural portion derived from the polyvalent carboxylic acid (a1) is preferably 50% by weight or more, particularly preferably 55 to 95% by weight, further preferably 60 to 90% by weight, and particularly preferably 70 to 85% by weight. If the content is too low, the adhesive tends to become too hard and the adhesive strength tends to decrease. If the content is too high, the adhesive tends to become too soft and the adhesive properties tend to decrease slightly.

[0021] The dimer acids are mainly composed of unsaturated fatty acid dimers having an average carbon number of 10 to 26, preferably unsaturated fatty acid dimers having an average carbon number of 12 to 24, and more preferably unsaturated fatty acid dimers having an average carbon number of 14 to 22. Specifically, they are dicarboxylic acids derived from unsaturated fatty acids such as oleic acids, linoleic acids, linolenic acids, and erucic acids. The term "main component" as used herein means a content of 90% by weight or more, preferably 95% by weight or more, and more preferably 98% by weight or more.

[0022] Examples of the dimer acids used in the present invention include dimer acids derived from the above unsaturated fatty acids (mainly having 36 or 44 carbon atoms) and hydrogenated products of the above dimer acids. Among them, hydrogenated products of dimer acids are preferred because they are easy to prevent crystallization.

[0023] That is, the structural moiety derived from the dimer acids of the present invention refers to a structural moiety in the polyester resin (A) obtained by polycondensation of the above dimer acids.

[0024] The structural portion derived from the polyvalent carboxylic acids (a1) of the present invention preferably contains a structural portion derived from an aliphatic dicarboxylic acid having 4 to 16 carbon atoms, in addition to the structural portion derived from the dimer acids. The number of carbon atoms is preferably 6 to 12.

[0025] Examples of the structural portion derived from an aliphatic dicarboxylic acid having 4 to 16 carbon atoms include structural portions derived from aliphatic dicarboxylic acids such as dimethylmalonic acids, succinic acids, glutaric acids, adipic acids, trimethyladipic acids, pimelic acids, 2,2-dimethylglutaric acids, azelaic acids, sebacic acids, fumaric acids, maleic acids, itaconic acids, thiodipropionic acids, diglycolic acids, and 1,9-nonanedicarboxylic acids.

[0026] The content of the structural moiety derived from the aliphatic dicarboxylic acid having 4 to 16 carbon atoms is preferably 10 to 80% by weight, more preferably 12 to 50% by weight, and particularly preferably 15 to 35% by weight, in the structural moiety derived from the polyvalent carboxylic acid (a1), from the viewpoint of compatibility with the carbodiimide group-containing compound (B) described later.

[0027] As the structural moiety derived from an aliphatic dicarboxylic acid having 4 to 16 carbon atoms, a structural moiety derived from a sebacic acid or a structural moiety derived from a succinic acid is preferred from the viewpoint of increasing the degree of bioplasticity. The content of the structural portion derived from sebacic acids and / or succinic acids in the structural portion derived from the polyvalent carboxylic acids (a1) is preferably 10 to 80% by weight, more preferably 12 to 50% by weight, and particularly preferably 15 to 35% by weight. If the content is too high, the crystallinity increases and the adhesive properties tend to be poor, whereas if the content is too low, the compatibility with the carbodiimide group-containing compound (B) tends to be poor and the haze tends to increase.

[0028] The structural portion derived from the polyvalent carboxylic acid (a1) other than the above may include, for example, a structural portion derived from a divalent dicarboxylic acid and a structural portion derived from a trivalent or higher polyvalent carboxylic acid. These structural portions may be included alone or in combination of two or more kinds. The structural portion derived from the divalent dicarboxylic acid and the structural portion derived from the trivalent or higher polyvalent carboxylic acid are 10% by weight or less, preferably 5% by weight or less, in the structural portion derived from the polyvalent carboxylic acid (a1). If the content is too high, the effect of the present invention tends not to be obtained.

[0029] Examples of the structural moiety derived from the divalent dicarboxylic acid include: Structural moieties derived from aliphatic dicarboxylic acids having 3 or less carbon atoms, such as malonic acids; Structural moieties derived from aromatic dicarboxylic acids such as phthalic acids, terephthalic acids, isophthalic acids, benzylmalonic acids, diphenic acids, 4,4'-oxydibenzoic acids, and further naphthalenedicarboxylic acids such as 1,8-naphthalenedicarboxylic acids, 2,3-naphthalenedicarboxylic acids, and 2,7-naphthalenedicarboxylic acids; Structural moieties derived from alicyclic dicarboxylic acids such as 1,3-cyclopentanedicarboxylic acids, 1,2-cyclohexanedicarboxylic acids, 1,3-cyclopentanedicarboxylic acids, 1,4-cyclohexanedicarboxylic acids, 2,5-norbornanedicarboxylic acids, and adamantanedicarboxylic acids; etc.

[0030] Examples of the structural portion derived from trivalent or higher polyvalent carboxylic acids include structural portions derived from trimellitic acids, pyromellitic acids, adamantanetricarboxylic acids, trimesic acids, and the like.

[0031] [Structural portion derived from polyol (a2)] The structural moiety derived from the polyol (a2) preferably contains a structural moiety derived from a dimer diol. The content of the structural portion derived from the dimer diol in the structural portion derived from the polyol (a2) is preferably 1 to 90% by weight, particularly preferably 20 to 85% by weight, further preferably 40 to 80% by weight, and particularly preferably 60 to 70% by weight. If the content is too low, the adhesive tends to become too hard and the adhesive strength tends to decrease. If the content is too high, the adhesive tends to become too soft and the adhesive properties tend to decrease slightly.

[0032] The structural moiety derived from the polyol (a2) of the present invention preferably contains a structural moiety derived from a polyol having 4 or less carbon atoms. The content is preferably 5% by weight or more, more preferably 10% by weight or more, even more preferably 50% by weight or more, and particularly preferably 70% by weight or more, in the structural portion derived from polyol (a2). If the content is too low, it tends to be difficult to obtain stable resin formation. The upper limit of the content of the structural portion derived from polyol having 4 or less carbon atoms is preferably 100% by weight.

[0033] Examples of the structural portion derived from a polyol having 4 or less carbon atoms include structural portions derived from aliphatic glycols having 4 or less carbon atoms, such as ethylene glycol, diethylene glycol, propylene glycol, 1,3-propanediol, 1,3-butanediol, and 1,4-butanediol.

[0034] The structural moiety derived from a polyol having 4 or less carbon atoms is preferably a structural moiety derived from ethylene glycol or a structural moiety derived from 1,3-propanediol, more preferably a structural moiety derived from ethylene glycol.Furthermore, a structural moiety derived from bioethylene glycol derived from a plant is also preferred. The number of carbon atoms is preferably 1 to 4, and more preferably 2 to 3.

[0035] By using a structural portion derived from a short polyol having 4 or less carbon atoms as the structural portion derived from the polyol (a2), the polarity of the polyester resin (A) containing a structural unit derived from a dimer acid and / or a dimer diol can be made relatively high. Therefore, the compatibility between the polyester resin (A) and the highly polar carbodiimide group-containing compound (B) can be increased, and an increase in haze tends to be suppressed. In addition, when a short polyol having 4 or less carbon atoms is used, the weight ratio of carboxylic acids having a high bioplasticity in the polyester resin (A) increases, and the bioplasticity tends to be increased.

[0036] Examples of the structural moiety derived from the polyol (a2) other than the above include structural moieties derived from divalent diols (excluding dimer diols and polyols having 4 or less carbon atoms), trivalent or higher polyols, etc. The structural moieties derived from the polyol (a2) other than the above may be contained alone or in combination of two or more kinds. The structural moiety derived from the divalent diol and the structural moiety derived from the trivalent or higher polyol are 10% by weight or less, preferably 5% by weight or less, in the structural moiety derived from the polyol (a2). If the content is too high, the effects of the present invention tend not to be obtained.

[0037] Examples of structural moieties derived from divalent diols (excluding dimer diols and polyols having 4 or less carbon atoms) include structural moieties derived from aliphatic diols such as triethylene glycol, dipropylene glycol, 2,4-dimethyl-2-ethylhexane-1,3-diol, 2-methyl-1,3-propanediol, 2,2-dimethyl-1,3-propanediol (neopentyl glycol), 2-ethyl-2-butyl-1,3-propanediol, 2-ethyl-2-isobutyl-1,3-propanediol, 1,5-pentanediol, 1,6-hexanediol, 3-methyl-1,5-pentanediol, and 2,2,4-trimethyl-1,6-hexanediol; Structural moieties derived from alicyclic diols such as 1,2-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, 1,4-cyclohexanedimethanol, spiroglycol, tricyclodecane dimethanol, adamantanediol, isosorbide, and 2,2,4,4-tetramethyl-1,3-cyclobutanediol; Structural moieties derived from aromatic diols such as 4,4'-thiodiphenol, 4,4'-methylenediphenol, bisphenol, bisphenolfluorene, 4,4'-dihydroxybiphenyl, o-, m- and p-dihydroxybenzene, 2,5-naphthalenediol, and p-xylenediol; and structural moieties derived from ethylene oxide and propylene oxide adducts thereof. Further examples include structural moieties derived from glycerol monostearate, etc.

[0038] Examples of the structural portion derived from the trivalent or higher polyol include structural portions derived from pentaerythritol, dipentaerythritol, tripentaerythritol, glycerin, trimethylolpropane, trimethylolethane, 1,3,6-hexanetriol, adamantanetriol, and the like.

[0039] Furthermore, in order to form reaction sites with the crosslinking agent (C) described below in the polyester resin (A) and increase the cohesive strength, it is also preferable that the polyester resin (A) contains a structural portion derived from an aliphatic polyhydric alcohol having a valence of three or more. Among these, it is particularly preferable that the polyester resin (A) contains a structural portion derived from trimethylolpropane, since gel formation is relatively unlikely to occur.

[0040] The content of the structural portion derived from the trihydric or higher aliphatic polyhydric alcohol in the structural portion derived from the polyol is preferably 5% by weight or less, more preferably 1% by weight or less, and particularly preferably 0.5% by weight or less. If the content of the structural portion derived from the trihydric or higher aliphatic polyhydric alcohol is too high, the production of the polyester resin (A) tends to become difficult.

[0041] [Other structural parts] Furthermore, the polyester resin (A) may contain, as other structural moieties, structural moieties derived from a compound having both a carboxylic acid and a hydroxyl group in the molecule (e.g., lactic acid, etc.) within a range that does not impair the effects of the present invention. However, since structural moieties derived from lactic acid are prone to hydrolysis, it is more preferable that they are not contained.

[0042] <Production of polyester resin (A)> In the present invention, the polyester resin (A) can be produced by polycondensation reaction of polyvalent carboxylic acids (a1) and polyol (a2) in the presence of a catalyst by a known method, and in the polycondensation reaction, an esterification reaction or an ester exchange reaction is carried out first, and then the polycondensation reaction is carried out. When it is not necessary to make the molecular weight high, the polyester resin (A) may be produced by only the esterification reaction or the ester exchange reaction.

[0043] The mixing ratio of the polyvalent carboxylic acids (a1) and the polyol (a2) is preferably 1 to 2 equivalents of the polyol (a2) per equivalent of the polyvalent carboxylic acids (a1), and particularly preferably 1.1 to 1.7 equivalents. If the mixing ratio of the polyol (a2) is too low, the acid value tends to be high, making it difficult to increase the molecular weight, and if it is too high, the yield tends to decrease.

[0044] [Polyvalent carboxylic acids (a1)] As the polyvalent carboxylic acid (a1), it is preferable to use a dimer acid, and the raw material for the dimer acid is usually a plant or beef tallow, and in the present invention, dimer acids derived from any raw material can be used, but it is preferable to use a raw material derived from a plant that is friendly to the global environment. By using a raw material derived from a plant, the bioplastic content of the polyester resin (A) can be increased. The amount of the dimer acids is 50% by weight or more, preferably 55 to 95% by weight, of the total amount of the polyvalent carboxylic acids (a1).

[0045] It is also preferable to use aliphatic dicarboxylic acids having 4 to 16 carbon atoms as the polycarboxylic acids (a1), and the amount of such aliphatic dicarboxylic acids having 4 to 16 carbon atoms is preferably 10 to 80% by weight, more preferably 12 to 50% by weight, based on the total amount of the polycarboxylic acids (a1).

[0046] Examples of the aliphatic dicarboxylic acids having 4 to 16 carbon atoms include aliphatic dicarboxylic acids such as dimethylmalonic acids, succinic acids, glutaric acids, adipic acids, trimethyladipic acids, pimelic acids, 2,2-dimethylglutaric acids, azelaic acids, sebacic acids, fumaric acids, maleic acids, itaconic acids, thiodipropionic acids, diglycolic acids, and 1,9-nonanedicarboxylic acids. These may be used alone or in combination of two or more. Among these, succinic acids and sebacic acids are preferred.

[0047] In addition, other polyvalent carboxylic acids (a1) that can be used include, for example, divalent dicarboxylic acids and trivalent or higher polyvalent carboxylic acids. These may be used alone or in combination of two or more kinds. The amount of the divalent dicarboxylic acids and trivalent or higher polyvalent carboxylic acids is 10% by weight or less, preferably 5% by weight or less, based on the total amount of the polyvalent carboxylic acids (a1).

[0048] Examples of the dicarboxylic acids include Aliphatic dicarboxylic acids having 3 or less carbon atoms, such as malonic acids; aromatic dicarboxylic acids such as phthalic acids, terephthalic acids, isophthalic acids, benzylmalonic acids, diphenic acids, 4,4'-oxydibenzoic acids, as well as naphthalenedicarboxylic acids such as 1,8-naphthalenedicarboxylic acids, 2,3-naphthalenedicarboxylic acids, 2,7-naphthalenedicarboxylic acids; alicyclic dicarboxylic acids such as 1,3-cyclopentanedicarboxylic acids, 1,2-cyclohexanedicarboxylic acids, 1,3-cyclopentanedicarboxylic acids, 1,4-cyclohexanedicarboxylic acids, 2,5-norbornanedicarboxylic acids, and adamantanedicarboxylic acids; etc.

[0049] Examples of the trivalent or higher polyvalent carboxylic acids include trimellitic acids, pyromellitic acids, adamantanetricarboxylic acids, and trimesic acids.

[0050] [Polyol (a2)] As the polyol (a2), it is preferable to use a dimer diol, and the raw material for the dimer diol can be obtained by reducing the above-mentioned dimer acids. The amount of the dimer diol blended is 1 to 90% by weight of the total amount of the polyol (a2).

[0051] The polyol (a2) of the present invention preferably contains a polyol having 4 or less carbon atoms in addition to the dimer diol. The content is 5 to 100% by weight based on the total amount of the polyol (a2).

[0052] Examples of the polyol having 4 or less carbon atoms include aliphatic glycols having 4 or less carbon atoms, such as ethylene glycol, diethylene glycol, propylene glycol, 1,3-propanediol, 1,3-butanediol, 1,4-butanediol, etc. These may be used alone or in combination of two or more kinds.

[0053] The polyol having 4 or less carbon atoms is preferably ethylene glycol or 1,3-propanediol, more preferably ethylene glycol. Furthermore, bioethylene glycol derived from plants is also preferred. The number of carbon atoms is preferably 1 to 4, and more preferably 2 to 3.

[0054] Examples of the polyol (a2) other than those mentioned above include divalent diols (excluding dimer diols and polyols having 4 or less carbon atoms), trivalent or higher polyols, etc. The polyol (a2) may be used alone or in combination of two or more kinds.

[0055] Examples of dihydric diols (excluding dimer diols and polyols having 4 or less carbon atoms) include aliphatic diols such as triethylene glycol, dipropylene glycol, 2,4-dimethyl-2-ethylhexane-1,3-diol, 2-methyl-1,3-propanediol, 2,2-dimethyl-1,3-propanediol (neopentyl glycol), 2-ethyl-2-butyl-1,3-propanediol, 2-ethyl-2-isobutyl-1,3-propanediol, 1,5-pentanediol, 1,6-hexanediol, 3-methyl-1,5-pentanediol, and 2,2,4-trimethyl-1,6-hexanediol; Alicyclic diols such as 1,2-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, 1,4-cyclohexanedimethanol, spiroglycol, tricyclodecane dimethanol, adamantanediol, isosorbide, and 2,2,4,4-tetramethyl-1,3-cyclobutanediol; Aromatic diols such as 4,4'-thiodiphenol, 4,4'-methylenediphenol, bisphenol, bisphenolfluorene, 4,4'-dihydroxybiphenyl, o-, m- and p-dihydroxybenzene, 2,5-naphthalenediol, and p-xylenediol; and ethylene oxide and propylene oxide adducts thereof. Further examples include glycerol monostearate.

[0056] Examples of the trihydric or higher polyol include pentaerythritol, dipentaerythritol, tripentaerythritol, glycerin, trimethylolpropane, trimethylolethane, 1,3,6-hexanetriol, and adamantanetriol.

[0057] The amount of the trihydric or higher polyol is preferably 5% by weight or less, more preferably 1% by weight or less, and particularly preferably 0.5% by weight or less, based on the polyol (a2). If the amount of the trihydric or higher polyol is too large, the production of the polyester resin (A) tends to become difficult.

[0058] [Other copolymer components] Furthermore, as another copolymerization component of the polyester resin (A), a compound having both a carboxylic acid and a hydroxyl group in the molecule (e.g., lactic acid, etc.) can be used within a range that does not impair the effects of the present invention. However, since lactic acid is easily hydrolyzed, it is more preferable not to use it.

[0059] In the present invention, it is also preferable to use polyethylene terephthalate (PET) as a copolymerization component of the polyester resin (A) in addition to the polyvalent carboxylic acids (a1) and polyols (a2). It is preferable to use so-called recycled PET. The polyethylene terephthalate is a polyester resin obtained by polymerizing terephthalic acids and ethylene glycol. Furthermore, the polyethylene terephthalate may be modified with substances such as isophthalic acids, phthalic anhydrides, adipic acids, cyclohexanedicarboxylic acids, sebacic acids, 1,3-butanediol, 1,4-butanediol, and cyclohexanedimethanol, as necessary. By using the polyethylene terephthalate, the polyester resin (A) contains structural parts derived from polyethylene terephthalate (for example, structural parts derived from terephthalic acids and ethylene glycol). The polyethylene terephthalate may be a virgin material or a recycled product, but it is preferable to use a recycled product from the viewpoint of the global environment.

[0060] [Esterification reaction or transesterification reaction] In the esterification reaction or transesterification reaction between the polyvalent carboxylic acids (a1) and the polyol (a2), a catalyst is usually used, and specific examples thereof include titanium-based catalysts such as tetraisopropyl titanate and tetrabutyl titanate, antimony-based catalysts such as antimony trioxide, germanium-based catalysts such as germanium dioxide, and catalysts such as zinc acetate, manganese acetate, and dibutyltin oxide, and one or more of these are used. Among these, antimony trioxide, tetrabutyl titanate, germanium dioxide, and zinc acetate are preferred from the viewpoint of the balance between the high catalytic activity and the hue of the resulting reaction product.

[0061] The amount of the catalyst is preferably 1 to 10,000 ppm, particularly preferably 10 to 5,000 ppm, and further preferably 20 to 3,000 ppm, based on the total copolymerization components (weight basis). If the amount is too small, the polymerization reaction tends not to proceed sufficiently, whereas if the amount is too large, there is no advantage such as shortening the reaction time, and side reactions tend to occur easily.

[0062] The reaction temperature during the esterification reaction or the ester exchange reaction is preferably 200 to 300° C., particularly preferably 210 to 280° C., and further preferably 220 to 260° C. If the reaction temperature is too low, the reaction tends not to proceed sufficiently, and if the reaction temperature is too high, side reactions such as decomposition tend to occur easily. The pressure during the reaction is usually normal pressure.

[0063] As reaction conditions for the polycondensation reaction carried out after the above-mentioned esterification reaction or transesterification reaction, it is preferable to further mix the same amount of the same catalyst as that used in the above-mentioned esterification reaction or transesterification reaction, set the reaction temperature at preferably 220 to 280° C., particularly preferably 230 to 270° C., and gradually reduce the pressure of the reaction system to finally carry out the reaction at 5 hPa or less. If the reaction temperature is too low, the reaction tends not to proceed sufficiently, and if it is too high, side reactions such as decomposition tend to occur easily. Thus, the polyester resin (A) is obtained.

[0064] [Physical properties of polyester resin (A)] Next, the physical properties of the polyester resin (A) obtained above will be described.

[0065] [Ester group concentration] The ester group concentration of the polyester resin (A) used in the present invention is preferably 2 mmol / g or more, more preferably 3 to 10 mmol / g, further preferably 3.1 to 7 mmol / g, and particularly preferably 3.2 to 5 mmol / g. If the ester group concentration is too low, the polyester resin (A) becomes soft and has poor dent resistance and processability.

[0066] The ester group concentration (mmol / g) refers to the number of moles of ester bonds in 1 g of polyester resin, and is calculated from the amount of each resin, for example. The calculation method is to divide the number of moles of the polyvalent carboxylic acid (a1) or the polyol (a2), whichever is less, by the total weight of the final product, and an example of the calculation formula is shown below. When the polyvalent carboxylic acids (a1) and the polyol (a2) are charged in equal molar amounts, either of the following calculation formulas may be used. Furthermore, when a monomer having both a carboxylic acid and a hydroxyl group is used, or when polyester is produced from caprolactone or the like, the calculation method will be changed appropriately.

[0067] <When the amount of polyvalent carboxylic acids (a1) is small> Ester group concentration (mmol / g) = [(A1 / a1 × m1 + A2 / a2 × m2 + A3 / a3 × m3 ) / Z] × 1000 A: Amount of polyvalent carboxylic acid (a1) (g) a: Molecular weight of polyvalent carboxylic acids (a1) m: number of carboxy groups per molecule of polyvalent carboxylic acids (a1) Z: Finished weight (g) <When the amount of polyol (a2) is small> Ester group concentration (mmol / g) = [(B1 / b1 × n1 + B2 / b2 × n2 + B3 / b3 × n3 ) / Z] × 1000 B: Amount of polyol (a2) (g) b: Molecular weight of polyol (a2) n: number of hydroxyl groups per molecule of polyol (a2) Z: Finished weight (g)

[0068] The concentration of the ester group and the structural site can be determined by a known method such as NMR. For example, the ester group concentration, composition and composition ratio of polyester resin (A) can be determined using a resonance frequency of 400 MHz. 1 H-NMR measurement (proton nuclear magnetic resonance spectroscopy), 13 This can be done by C-NMR measurement (carbon-type nuclear magnetic resonance spectroscopy).

[0069] Examples of methods for adjusting the ester group concentration within a predetermined range include a method of selecting a polyol having 4 or less carbon atoms as the polyol (a2), a method of increasing the content of linear carboxylic acids as the polyvalent carboxylic acids (a1), and a method of combining both of these.

[0070] [Bioplastic content] The bioplastic degree of the polyester resin (A) used in the present invention is preferably 60% or more, more preferably 65% ​​or more, even more preferably 70% or more, and particularly preferably 80% or more. If the bioplastic degree is low, the reduction of the environmental load tends to be insufficient. The upper limit of the bioplastic degree is 100%.

[0071] Here, the bioplastic degree of the polyester resin (A) refers to the weight ratio of the portion of the resin in which the plant-derived raw materials used in producing the polyester resin (A) are incorporated relative to the total weight of the polyester resin (A), and is calculated as follows: The bioplastic degrees of the polyvalent carboxylic acids (a1), polyols (a2) and other components (e.g., compounds having a carboxyl group and a hydroxyl group in the molecule) are calculated from the weighted average of the respective bioplastic degrees. The bioplastic degree may be any value obtained by any one of the calculation methods described below, as long as it falls within the above range.

[0072] (Calculation method) <When polycondensation reaction is involved> Bioplastic content (%)=[(number of moles of carbon of plant-derived monomer calculated from the molar ratio of polyvalent carboxylic acids (a1) and polyol (a2) in polyester resin (A)) / (number of moles of carbon of all constituent monomers in polyester resin (A)]×100

[0073] <When no polycondensation reaction is involved> Bioplastic content (%) = [(number of moles of carbon of plant-derived monomer in polyester resin (A)) / (number of moles of carbon of all constituent monomers in polyester resin (A)] × 100

[0074] The bioplastic degree can also be determined by analyzing the composition ratio by NMR and calculating the carbon number of the plant-derived monomer / the total carbon number.

[0075] Furthermore, the bioplastic content can also be measured by the method described in “Technology for determining the origin of biofuels using natural radioactive carbon C-14” in Tokyo Metropolitan Industrial Technology Research Center Research Report, No. 4, 2009.

[0076] Methods for adjusting the bioplastic degree within a predetermined range include using mainly plant-derived polyvalent carboxylic acids (a1) or plant-derived polyols (a2). In terms of efficiently increasing the bioplastic degree, it is particularly preferable to use plant-derived polyvalent carboxylic acids (a1).

[0077] [Crystal melting heat] The heat of crystalline fusion of the polyester resin (A) measured by a differential scanning calorimeter (DSC) is preferably 10 J / g or less, more preferably 5 J / g or less, even more preferably 2 J / g or less, and particularly preferably no heat of crystalline fusion. If the heat of crystalline fusion is too large, crystallinity will be produced, and the storage stability of the resin solution will tend to be poor, and the stability and adhesive properties at low temperatures when made into an adhesive sheet will tend to be poor.

[0078] Examples of methods for adjusting the heat of crystalline fusion within a predetermined range include a method of appropriately using polyvalent carboxylic acids (a1) having an alkyl group on the side chain or polyols (a2) having an alkyl group on the side chain, and a method of using three or more, preferably four or more, copolymerizable monomer components.

[0079] The heat of crystalline fusion means the energy consumed when a crystallized substance is heated and melted, and can be measured by a differential scanning calorimeter (DSC).

[0080] [Weight average molecular weight] The weight average molecular weight of the polyester resin (A) is preferably 2000 to 500000, more preferably 10000 to 300000, and particularly preferably 50000 to 150000. If the weight average molecular weight is too large, the handleability decreases, so a large amount of solvent is required, which tends to increase the environmental load, whereas if the weight average molecular weight is too small, the adhesive properties tend to decrease.

[0081] The weight-average molecular weights shown above are those calculated based on the molecular weight of standard polystyrene. The high-performance liquid chromatograph (HLC-8320GPC, manufactured by Tosoh Corporation) was used with a column: TSKgel Super Multipore HZ-M (molecular weight exclusion limit: 2×10 6 The measurement is performed using two columns in series (theoretical plate number: 16,000 plates / column, filler material: styrene-divinylbenzene copolymer, filler particle size: 4 μm).

[0082] [Acid value] The acid value of the polyester resin (A) is preferably 10 mgKOH / g or less in terms of preventing hydrolysis and increasing durability, more preferably 5 mgKOH / g or less, particularly preferably 2 mgKOH / g or less, and especially preferably 1 mgKOH / g or less. If the acid value is too large, durability tends to decrease. The acid value can be adjusted, for example, by increasing the ratio of polyol (a2) during the esterification reaction or transesterification reaction, or by adjusting the reaction conditions. The lower limit of the acid value is usually 0 mgKOH / g.

[0083] The acid value of the polyester resin (A) is determined by neutralization titration in accordance with JIS K0070. In the present invention, the acid value means the content of carboxy groups in the polyester resin (A). The carboxy groups include those in a carboxylate ion state in which the carboxy groups are neutralized with a basic compound.

[0084] [Glass transition temperature (Tg)] The glass transition temperature (Tg) of the polyester resin (A) is preferably −90 to 20° C., particularly preferably −80 to 0° C., further preferably −70 to −20° C., and particularly preferably −60 to −30° C. If the glass transition temperature (Tg) is too high, the adhesive property of the resulting pressure-sensitive adhesive composition tends to decrease, whereas if it is too low, the heat resistance and cohesive strength tend to decrease. The glass transition temperature can be adjusted, for example, by introducing an aromatic skeleton or by changing the alkyl chain length of the polyvalent carboxylic acid (a1) or the polyol (a2).

[0085] The glass transition temperature (Tg) is measured using a differential scanning calorimeter DSC Q20 manufactured by TA Instruments, Inc. The measurement temperature range is −90 to 100° C., and the temperature rise rate is 10° C. / min.

[0086] The pressure-sensitive adhesive composition [I] used in the present invention contains the above-mentioned polyester resin (A) and a carbodiimide group-containing compound (B). The carbodiimide group-containing compound (B) will be described below.

[0087] <Carbodiimide Group-Containing Compound (B)> As the carbodiimide group-containing compound (B) used in the present invention, a known carbodiimide having one or more carbodiimide groups (-N=C=N-) in the molecule can usually be used. However, in terms of improving durability under high temperature and high humidity conditions, a compound having two or more carbodiimide groups in the molecule, i.e., a polyvalent carbodiimide compound, is preferred, and in particular a compound having three or more carbodiimide groups in the molecule, further five or more, and particularly seven or more. The number of carbodiimide groups in a molecule is usually 50 or less. If there are too many carbodiimide groups, the molecular structure becomes too large, and compatibility tends to decrease.

[0088] As the carbodiimide group-containing compound (B) used in the present invention, it is preferable to use one having a high weight average molecular weight from the viewpoint of hydrolysis resistance. The weight average molecular weight of the carbodiimide group-containing compound (B) is preferably 1000 or more, more preferably 2000 or more, and even more preferably 3000 or more. The upper limit of the weight average molecular weight is usually 50000.

[0089] The carbodiimide group-containing compound (B) preferably has low volatility, and therefore it is preferable to use one having a high number average molecular weight, which is usually 300 to 10,000, and preferably 1,000 to 5,000.

[0090] If the molecular weight of the carbodiimide group-containing compound (B) is too small, the hydrolysis resistance tends to decrease, whereas if the molecular weight is too large, the compatibility with the polyester resin (A) tends to decrease.

[0091] The carbodiimide equivalent of the carbodiimide group-containing compound (B) is preferably 50 to 10,000, particularly 100 to 1,000, and further preferably 150 to 500. The carbodiimide equivalent indicates the chemical formula weight per one carbodiimide group.

[0092] The content of the carbodiimide group-containing compound (B) is preferably 0.01 to 10 parts by weight, particularly preferably 0.1 to 5 parts by weight, and further preferably 0.2 to 3 parts by weight, based on 100 parts by weight of the polyester resin (A). If the content is too high, turbidity tends to occur due to poor compatibility with the polyester resin (A), and if the content is too low, sufficient durability tends to be difficult to obtain.

[0093] The content of the carbodiimide group-containing compound (B) is preferably optimized according to the acid value of the polyester resin (A), and the molar ratio (y) of the total number of moles of the functional groups of the carbodiimide group-containing compound (B) in the adhesive composition [I] to the total number of moles of the acidic functional groups of the polyester resin (A) in the adhesive composition [I] [(y) / (x)] is preferably 0.5≦(y) / (x), particularly preferably 1≦(y) / (x)≦1000, and more preferably 1.5≦(y) / (x)≦100. If the molar ratio of (y) to (x) is too low, the moisture and heat resistance tends to decrease. If the molar ratio of (y) to (x) is too high, the compatibility with the polyester resin (A) tends to decrease, and the adhesive strength, cohesive strength, and durability tend to decrease.

[0094] As the carbodiimide group-containing compound (B), it is also preferable to use a polycarbodiimide-based compound (B1) produced by subjecting a diisocyanate to a decarboxylation condensation reaction in the presence of a carbodiimide catalyst.

[0095] [Polycarbodiimide compound (B1)] The polycarbodiimide compound (B1) can be obtained by subjecting an organic diisocyanate compound to a condensation reaction. Examples of the organic diisocyanate compound include aromatic diisocyanate compounds such as 1,5-naphthylene diisocyanate, 4,4'-diphenylmethane diisocyanate, 4,4'-diphenyldimethylmethane diisocyanate, 1,3-phenylene diisocyanate, 1,4-phenylene diisocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, a mixture of 2,4-tolylene diisocyanate and 2,6-tolylene diisocyanate, xylylene diisocyanate, and tetramethylxylylene diisocyanate; Examples of the diisocyanates include acyclic aliphatic diisocyanates such as hexamethylene diisocyanate, and aliphatic diisocyanates such as cyclohexane-1,4-diisocyanate, isophorone diisocyanate, dicyclohexylmethane-4,4'-diisocyanate, methylcyclohexane diisocyanate, and cyclic aliphatic diisocyanates such as 2,5(2,6)-bis(isocyanatomethyl)bicyclo[2.2.1]heptane. These may be used alone or in combination of two or more. Among these, aromatic diisocyanate compounds are preferred, and tetramethylxylene diisocyanate is more preferred, in that they can provide a pressure-sensitive adhesive composition having excellent resistance to moist heat.

[0096] The above organic diisocyanate compound can be subjected to a decarboxylation condensation reaction in the presence of a known carbodiimidization catalyst in a conventional manner to obtain a polycarbodiimide compound (B1).

[0097] The polycarbodiimide compound (B1) is preferably an aromatic polycarbodiimide compound, since it can be used to produce a pressure-sensitive adhesive that exhibits little haze change even under high-temperature and high-humidity conditions and has excellent resistance to moist heat.

[0098] Furthermore, the polycarbodiimide compound (B1) used in the present invention is preferably a polycarbodiimide compound (B1-1) in which at least one of the terminal isocyanate groups of the polycarbodiimide compound (B1) is substituted with a substituent derived from the hydrophilic organic compound (α).

[0099] [Polycarbodiimide compound (B1) in which at least one of the terminal isocyanate groups has been substituted with a substituent derived from a hydrophilic organic compound (α) (B1-1)] Next, a polycarbodiimide compound (B1-1) in which at least one of the terminal isocyanate groups of the polycarbodiimide compound (B1) is substituted with a substituent derived from the hydrophilic organic compound (α) will be described. First, the hydrophilic organic compound (α) will be described.

[0100] [Hydrophilic organic compound (α)] The hydrophilic organic compound (α) is a compound having a substituent with an active hydrogen that is reactive with the terminal isocyanate group of the polycarbodiimide compound (B1), and further having one or more heteroatoms in the molecule in addition to the substituent.

[0101] Examples of the substituent having active hydrogen reactive with the isocyanate group include a hydroxyl group, a primary amino group, a secondary amino group, an imino group, an isocyanate group, and a carboxyl group. Among them, a hydroxyl group, a primary amino group, a secondary amino group, and an imino group are preferred. These substituents may be contained alone or in combination of two or more in the hydrophilic organic compound (α).

[0102] The number of the substituents having active hydrogen reactive with the isocyanate group in the hydrophilic organic compound (α) is usually 2 or less, and preferably 1. In addition, the substituents are preferably located at the terminals of the hydrophilic organic compound (α).

[0103] Examples of the compound having a substituent having active hydrogen reactive with the isocyanate group and further having one or more heteroatoms in the molecule in addition to the substituent include an oxyalkylene structure-containing compound, a hydroxypolyester structure-containing compound, a hydroxyalkylsulfonic acid structure-containing compound, a dialkylaminoalcohol structure-containing compound, a hydroxycarboxylic acid alkyl ester structure-containing compound, a dialkylaminoalkylamine structure-containing compound, etc. Among these, an oxyalkylene structure-containing compound is preferred.

[0104] In addition, the ends of the hydrophilic organic compound (α) are preferably blocked with an alkoxy group or a phenoxy group.

[0105] Among these, as the hydrophilic organic compound (α), a compound containing an oxyalkylene structure end-blocked with an alkoxy group or a phenoxy group is preferred, since it causes little change in haze even under high temperature and high humidity conditions.

[0106] The above-mentioned oxyalkylene structure-containing compound end-blocked with an alkoxy group or a phenoxy group includes, for example, a compound represented by the following formula (1). R1-O-(CH2-CHR2-O)mH (1) In the above formula (1), R1 represents an alkyl group having 1 to 4 carbon atoms or a phenyl group, R2 represents a hydrogen atom or a methyl group, and m is an integer of 4 to 100.

[0107] Examples of the alkyl group having 1 to 4 carbon atoms include a methyl group, an ethyl group, a propyl group, an isopropyl group, an n-butyl group, an s-butyl group, an isobutyl group, and a t-butyl group.

[0108] Specific examples of the compound represented by the above formula (1) include polyethylene glycol monomethyl ether, polyethylene glycol monoethyl ether, polypropylene glycol monomethyl ether, polypropylene glycol monoethyl ether, polypropylene glycol monophenyl ether, etc. Among these, polyethylene glycol monomethyl ether is preferred.

[0109] The weight-average molecular weight of the hydrophilic organic compound (α) is preferably 200 or more, more preferably 400 or more. The upper limit of the weight-average molecular weight is usually 5000 or less, preferably 4000 or less, more preferably 2000 or less, and even more preferably 1000 or less. If the weight-average molecular weight is too small, the compatibility with the polyester resin decreases, and furthermore, the haze change under high temperature and high humidity conditions tends to increase. If the weight-average molecular weight is too large, the adhesive strength tends to decrease.

[0110] The polycarbodiimide compound (B1-1) in which at least one of the terminal isocyanate groups of the polycarbodiimide compound (B1) is substituted with a substituent derived from the hydrophilic organic compound (α) can be obtained by reacting the polycarbodiimide compound (B1) with the hydrophilic organic compound (α).

[0111] The reaction between the polycarbodiimide compound (B1) and the hydrophilic organic compound (α) is carried out by heating the polycarbodiimide compound (B1) usually to 50 to 200°C, preferably 100 to 180°C, adding the hydrophilic organic compound (α), and then further reacting at 80 to 200°C for 0.5 to 5 hours.

[0112] In this manner, a polycarbodiimide compound (B1-1) can be obtained in which at least one of the terminal isocyanate groups of the polycarbodiimide compound (B1) is substituted with a substituent derived from the hydrophilic organic compound (α).

[0113] Examples of commercially available polycarbodiimide compounds (B1) include Carbodilite (registered trademark) V-09GB, V-02B, V-04K, and V-04PF manufactured by Nisshinbo Chemical Inc., and Elastostab H01 manufactured by BASF, and among these, Carbodilite V-04PF is preferred.

[0114] The pressure-sensitive adhesive composition [I] used in the present invention preferably further contains a crosslinking agent (C), a urethanization catalyst (D) and an antioxidant (E).

[0115] [Crosslinking agent (C)] By incorporating a crosslinking agent (C) in the pressure-sensitive adhesive composition [I], the polyester resin (A) is crosslinked with the crosslinking agent (C) to provide excellent cohesive strength, thereby improving the performance of the pressure-sensitive adhesive.

[0116] Examples of such crosslinking agents (C) include compounds having functional groups that react with at least one of the hydroxyl group and the carboxyl group contained in the polyester resin (A), such as polyisocyanate compounds and polyepoxy compounds. In addition, polyfunctional acrylic monomers and urethane acrylate oligomers that increase the cohesive strength even if they do not react with the polyester resin (A) can also be used. Among these, it is particularly preferable to use polyisocyanate compounds, since they can achieve a good balance between adhesive strength, mechanical strength, and heat resistance.

[0117] Examples of such polyisocyanate compounds include polyisocyanates such as tetramethylene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, tolylene diisocyanate, diphenylmethane diisocyanate, hydrogenated diphenylmethane diisocyanate, xylylene diisocyanate, hydrogenated xylylene diisocyanate, tetramethylxylylene diisocyanate, 1,5-naphthalene diisocyanate, and triphenylmethane triisocyanate. In addition, examples of such polyisocyanate compounds include adducts of the above polyisocyanates with polyol compounds such as trimethylolpropane, and biuret and isocyanurate compounds of these polyisocyanate compounds. The above polyisocyanate compounds may also be used in which the isocyanate portion is blocked with phenol, lactam, or the like. These crosslinking agents (C) may be used alone or in a mixture of two or more.

[0118] Of such polyisocyanate compounds, aliphatic polyisocyanate compounds are preferred, and it is further preferred to use a difunctional aliphatic isocyanate compound, in that this improves compatibility with the polyester resin (A) and reduces haze.

[0119] The content of the crosslinking agent (C) can be appropriately selected depending on the molecular weight of the polyester resin (A) and the intended use, but it is usually preferable that the crosslinking agent (C) is contained in a ratio of 0.2 to 10 equivalents of reactive groups contained in the crosslinking agent (C) per equivalent of at least one of the hydroxyl group and the carboxyl group contained in the polyester resin (A), particularly preferably 0.5 to 5 equivalents, and further preferably 0.5 to 3 equivalents. If the equivalent number of reactive groups contained in the crosslinking agent (C) is too small, the cohesive strength tends to decrease, and if it is too large, the flexibility tends to decrease.

[0120] The content of the crosslinking agent (C) is preferably 0.01 to 10 parts by weight, more preferably 0.1 to 8 parts by weight, further preferably 0.5 to 6 parts by weight, and especially preferably 1 to 4 parts by weight, based on 100 parts by weight of the polyester resin (A). If the content of the crosslinking agent is low, the cohesive strength tends to decrease, whereas if the content is too high, the flexibility tends to decrease and the required adhesive strength tends to be difficult to obtain.

[0121] In the reaction between the polyester resin (A) and the crosslinking agent (C), organic solvents that do not have functional groups that react with these components, such as esters such as ethyl acetate and butyl acetate, ketones such as methyl ethyl ketone and methyl isobutyl ketone, aromatics such as toluene and xylene, etc., can be used alone or in combination of two or more of them.

[0122] [Urethanization catalyst (D)] The pressure-sensitive adhesive composition [I] used in the present invention preferably contains a urethanization catalyst (D) in terms of reaction rate.

[0123] Examples of the urethanization catalyst (D) include organometallic compounds, tertiary amine compounds, etc. These can be used alone or in combination of two or more kinds.

[0124] Examples of the organometallic compound include zirconium-based compounds, iron-based compounds, tin-based compounds, titanium-based compounds, lead-based compounds, cobalt-based compounds, and zinc-based compounds.

[0125] Examples of the zirconium compound include zirconium naphthenate and zirconium acetylacetonate. Examples of the iron-based compound include iron acetylacetonate and iron 2-ethylhexanoate. Examples of the tin compounds include dibutyltin dichloride, dibutyltin oxide, and dibutyltin dilaurate. Examples of the titanium-based compound include dibutyltitanium dichloride, tetrabutyltitanium, and butoxytitanium trichloride. Examples of the lead-based compounds include lead oleate, lead 2-ethylhexanoate, lead benzoate, and lead naphthenate. Examples of the cobalt-based compound include cobalt 2-ethylhexanoate and cobalt benzoate. Examples of the zinc-based compound include zinc naphthenate and zinc 2-ethylhexanoate.

[0126] Examples of the tertiary amine compound include triethylamine, triethylenediamine, and 1,8-diazabicyclo-(5,4,0)-undecene-7.

[0127] Among these urethane catalysts (D), in terms of reaction speed and pot life of the adhesive layer, organometallic compounds are preferred, and zirconium compounds are particularly preferred. Furthermore, the urethane catalyst (D) is preferably used in combination with acetylacetone as a catalytic action inhibitor. The inclusion of acetylacetone is preferred in that it inhibits catalytic action at low temperatures and extends the pot life.

[0128] The content of the urethane catalyst (D) is preferably 0.0001 to 1 part by weight, more preferably 0.001 to 0.1 part by weight, and even more preferably 0.01 to 0.05 part by weight, based on 100 parts by weight of the polyester resin (A). If the content is too low, the aging time until the crosslinking reaction is completed tends to be long, and if the content is too high, the adhesive properties tend to decrease.

[0129] [Antioxidants (E)] The pressure-sensitive adhesive composition [I] used in the present invention preferably contains an antioxidant (E) in order to increase the stability of the resin.

[0130] Examples of the antioxidant (E) include hindered phenol-based antioxidants, amine-based antioxidants, sulfur-based antioxidants, phosphoric acid-based antioxidants, etc. Among them, at least one selected from the group consisting of hindered phenol-based antioxidants, amine-based antioxidants, and phosphoric acid-based antioxidants is preferred, and an antioxidant consisting of a hindered phenol-based compound is particularly preferred.

[0131] Examples of the hindered phenol-based antioxidants include antioxidants having a hindered phenol structure in which a group with large steric hindrance, such as a tertiary butyl group, is bonded to at least one of the carbon atoms adjacent to the carbon atom on the aromatic ring to which the phenolic hydroxyl group is bonded.

[0132] The content of the antioxidant (E) is preferably 0.01 to 10 parts by weight, more preferably 0.03 to 8 parts by weight, and even more preferably 0.05 to 5 parts by weight, based on 100 parts by weight of the polyester resin (A). If the content is too low, adhesive residue on the adherend tends to be easily generated, and if the content is too high, the adhesive properties tend to decrease.

[0133] In the adhesive composition [I] used in the present invention, in addition to the above-mentioned polyester resin (A), carbodiimide group-containing compound (B), crosslinking agent (C), urethanization catalyst (D), and antioxidant (E), additives such as hydrolysis inhibitors other than the carbodiimide group-containing compound (B), tackifier resins, softeners, ultraviolet absorbers, stabilizers, antistatic agents, and other additives such as inorganic or organic fillers, powders such as metal powders, and pigments, and particulate additives can be blended within a range that does not impair the effects of the present invention (for example, 10% by weight or less of the adhesive composition [I]). In addition, it may contain a small amount of impurities contained in the manufacturing raw materials of the components of the adhesive composition [I]. These can be used alone or in combination of two or more.

[0134] The pressure-sensitive adhesive composition [I] can be obtained, for example, by preparing the polyester resin (A), the carbodiimide group-containing compound (B) and necessary optional components, etc., and mixing and dispersing them during the production of the polyester resin (A), or by mixing them into the polyester resin (A) and dispersing them using a mixing roller, etc. At this time, they may be dispersed as a solution using a solvent, or may be dispersed without a solvent.

[0135] <Adhesive composition [I]> The pressure-sensitive adhesive composition [I] preferably has a bioplasticity of 60% or more from the viewpoint of reducing the environmental load, more preferably 70% or more, particularly preferably 80% or more, particularly preferably 85% or more, and most preferably 90% or more. The bioplasticity of the pressure-sensitive adhesive composition [I] can be adjusted by the types and amounts of the polyester resin (A) and other blending components.

[0136] The bioplasticity of the pressure-sensitive adhesive composition [I] is the ratio of the weight of the plant-derived raw materials used in producing the pressure-sensitive adhesive composition [I] to the total weight of the pressure-sensitive adhesive composition [I], and can be calculated, for example, by the following formula. Bioplastic content (%)=[(Bioplastic content of each plant-derived raw material used in producing the adhesive composition [I])×(weight of each plant-derived raw material used in producing the adhesive composition [I])] / (total weight of the adhesive composition [I])×100

[0137] The bioplasticity of the pressure-sensitive adhesive composition [I] can also be measured by the above-mentioned method using NMR or method using natural radioactive carbon C-14. The bioplasticity obtained by any one of the above-mentioned calculation methods may be within the above-mentioned range.

[0138] <Adhesive> The pressure-sensitive adhesive of the present invention is obtained by crosslinking the above-mentioned pressure-sensitive adhesive composition [I].

[0139] The above pressure-sensitive adhesive has a haze of 5% or less when made into a 50 μm thick pressure-sensitive adhesive layer according to the pressure-sensitive adhesive sheet manufacturing method described below. The haze is preferably 4% or less, and particularly preferably 2% or less. In other words, the pressure-sensitive adhesive of the present invention has excellent transparency even when made into a thick pressure-sensitive adhesive layer. The haze is a value measured using a Haze Material NDH2000 (manufactured by Nippon Denshoku Industries Co., Ltd.) The haze meter complies with JIS K7361-1.

[0140] The haze of the adhesive layer using the above adhesive can be controlled to 5% or less by achieving a comprehensive balance in, for example, adjusting the amount of dimer acids and aliphatic dicarboxylic acids incorporated, the type of polyol (a2), adjusting the ester bond concentration, the type of carbodiimide group-containing compound (B), and the like. Among these, a method of using a polyol having 4 or less carbon atoms as the polyol (a2) and a method of increasing the ester group concentration of the polyester resin as much as possible (particularly 2 mmol / g or more) are effective. Other effective methods include a method of using as the carbodiimide group-containing compound (B) a polycarbodiimide compound (B1) in which at least one of the terminal isocyanate groups is substituted with a substituent derived from the hydrophilic organic compound (α) (B1-1), and a method of using as the crosslinking agent (C) an aliphatic isocyanate (particularly a bifunctional aliphatic isocyanate).

[0141] The gel fraction of the pressure-sensitive adhesive is preferably 10% by weight or more from the viewpoint of durability and adhesive strength, more preferably 20-80% by weight, even more preferably 30-60% by weight, and especially preferably 40-50% by weight. If the gel fraction is too low, the cohesive strength tends to decrease, leading to a decrease in holding power. If the gel fraction is too high, the cohesive strength tends to increase, leading to a decrease in adhesive strength.

[0142] The gel fraction is an indication of the degree of crosslinking, and is calculated, for example, by the following method: the pressure-sensitive adhesive of the present invention is wrapped in a 200-mesh SUS wire netting and immersed in toluene at 23°C for 24 hours, and the gel fraction is the weight percentage of the insoluble pressure-sensitive adhesive component remaining in the wire netting after immersion relative to the weight of the pressure-sensitive adhesive component before immersion.

[0143] In addition, the retention rate (G2 / G1) of the gel fraction (G2) of the pressure-sensitive adhesive of the present invention after the pressure-sensitive adhesive is allowed to stand for 500 hours at 85°C and 85% RH relative to the initial gel fraction (G1) is preferably 70% or more, and more preferably 80% or more.

[0144] The pressure-sensitive adhesive of the present invention has excellent adhesive strength, durability under high temperature and high humidity conditions, and transparency, and therefore can be suitably used as a pressure-sensitive adhesive for attaching optical members or window films.

[0145] The pressure-sensitive adhesive sheet of the present invention has a pressure-sensitive adhesive layer containing the above-mentioned pressure-sensitive adhesive, and such a pressure-sensitive adhesive layer is preferably formed on one or both sides of a supporting substrate. In the present invention, the term "sheet" is used to include the meanings of "film" and "tape."

[0146] <Adhesive sheet> The pressure-sensitive adhesive sheet can be obtained by a known general pressure-sensitive adhesive sheet manufacturing method, for example, a step of applying the pressure-sensitive adhesive composition [I] to a substrate, a step of drying the applied pressure-sensitive adhesive composition [I] to form a pressure-sensitive adhesive layer, a step of laminating a release sheet to the surface of the pressure-sensitive adhesive layer opposite to the substrate, etc. Furthermore, the pressure-sensitive adhesive sheet may be aged as necessary.

[0147] In addition to the above method, a pressure-sensitive adhesive sheet can be obtained by a process of coating the pressure-sensitive adhesive composition [I] on a release sheet, a process of drying the coated pressure-sensitive adhesive composition [I] to form a pressure-sensitive adhesive layer, and a process of laminating a substrate to the surface of the pressure-sensitive adhesive layer opposite to the release sheet. If necessary, the pressure-sensitive adhesive sheet may be aged.

[0148] Furthermore, in the above method, a substrate-less double-sided pressure-sensitive adhesive sheet can be produced by forming a pressure-sensitive adhesive layer on a release sheet and laminating a release sheet instead of a substrate to the surface of the pressure-sensitive adhesive layer opposite the release sheet.

[0149] Examples of the substrate include polyester resins such as polyethylene naphthalate, polyethylene terephthalate, polybutylene terephthalate, and polyethylene terephthalate / isophthalate copolymer; polyolefin resins such as polyethylene, polypropylene, and polymethylpentene; polyethylene fluoride resins such as polyvinyl fluoride, polyvinylidene fluoride, and polyethylene fluoride; polyamides such as nylon 6 and nylon 6,6; vinyl polymers such as polyvinyl chloride, polyvinyl chloride / vinyl acetate copolymer, ethylene-vinyl acetate copolymer, ethylene-vinyl alcohol copolymer, polyvinyl alcohol, and vinylon; cellulose resins such as cellulose triacetate and cellophane; acrylic resins such as polymethyl methacrylate, polyethyl methacrylate, polyethyl acrylate, and polybutyl acrylate; polystyrene; polycarbonate; polyarylate; polyimide; and sheets made of at least one synthetic resin selected from the group consisting of cycloolefin polymers; metal foils of aluminum, copper, and iron; paper such as fine paper and glassine paper; and woven and nonwoven fabrics made of glass fiber, natural fibers, synthetic fibers, and the like. These substrates can be used as a single layer or as a multi-layer structure in which two or more types are laminated.

[0150] Among these, substrates made of polyethylene terephthalate and polyimide are particularly preferred, with polyethylene terephthalate being particularly preferred in terms of excellent adhesion to pressure-sensitive adhesives.

[0151] As the release sheet, for example, a sheet made of any of the various synthetic resins exemplified above as the base material, paper, cloth, nonwoven fabric, etc. that has been subjected to a release treatment can be used. As the release sheet, it is preferable to use a silicone-based release sheet.

[0152] The thickness of the above-mentioned substrate and release sheet is, for example, preferably from 1 to 1000 μm, particularly preferably from 2 to 500 μm, and further preferably from 3 to 300 μm.

[0153] When the pressure-sensitive adhesive composition [I] is applied onto a substrate or a release sheet, it is preferable to adjust the viscosity of the pressure-sensitive adhesive composition [I] using a solvent.

[0154] As the solvent, for example, organic solvents such as esters such as ethyl acetate and butyl acetate, ketones such as methyl ethyl ketone and methyl isobutyl ketone, and aromatics such as toluene and xylene can be used. These can be used alone or in combination of two or more. Among them, ethyl acetate is preferred.

[0155] In addition, the content of the solvent in the pressure-sensitive adhesive composition [I] is preferably 10% by weight or less in terms of reducing the environmental load.

[0156] The pressure-sensitive adhesive composition may be applied using, for example, a gravure roll coater, a reverse roll coater, a kiss roll coater, a dip roll coater, a bar coater, a knife coater, a spray coater, a comma coater, or the like.

[0157] The drying conditions for drying the applied pressure-sensitive adhesive composition [I] are preferably a drying temperature of 60 to 140° C., particularly preferably 80 to 120° C., and a drying time of 0.5 to 30 minutes, particularly preferably 1 to 5 minutes.

[0158] The conditions for curing the pressure-sensitive adhesive sheet are typically room temperature (23°C) to 70°C, and typically 1 to 30 days; specifically, the curing may be performed under conditions such as 23°C for 1 to 20 days, preferably 23°C for 3 to 14 days, or 40°C for 1 to 10 days.

[0159] The thickness of the adhesive layer of the adhesive sheet and substrate-less double-sided adhesive sheet of the present invention thus obtained is preferably 2 to 500 μm, particularly preferably 5 to 200 μm, and further preferably 10 to 100 μm. If the thickness of the adhesive layer is too thin, the adhesive strength tends to decrease, while if it is too thick, it becomes difficult to apply uniformly and problems such as air bubbles in the coating film tend to occur. When considering impact absorption, it is preferable to set the thickness to 50 μm or more.

[0160] The thickness of the adhesive layer is determined by subtracting the measured thickness of the components other than the adhesive layer from the measured thickness of the entire adhesive sheet using a Mitutoyo ID-C112B.

[0161] Furthermore, such a pressure-sensitive adhesive sheet may be protected by providing a release sheet on the outer side of the pressure-sensitive adhesive layer, if necessary. In a pressure-sensitive adhesive sheet in which the pressure-sensitive adhesive layer is formed on one side of a substrate, the substrate may be subjected to a release treatment on the side opposite to the pressure-sensitive adhesive layer, and the release-treated surface may be used to protect the pressure-sensitive adhesive layer.

[0162] When using the resulting pressure-sensitive adhesive sheet or substrate-less double-sided pressure-sensitive adhesive sheet, the release sheet is peeled off from the pressure-sensitive adhesive layer, and the pressure-sensitive adhesive layer is attached to an adherend.

[0163] The pressure-sensitive adhesive of the present invention can be used for bonding various members, and is particularly suitable for use as a single-sided or double-sided pressure-sensitive adhesive sheet for bonding optical members, or a double-sided pressure-sensitive adhesive sheet for bonding window films.

[0164] Examples of the optical components include transparent electrode films such as an ITO electrode film and an inorganic or organic conductive film such as polythiophene, a polarizing plate, a retardation plate, an elliptically polarizing plate, an optical compensation film, a brightness enhancing film, an electromagnetic wave shielding film, a near-infrared absorbing film, and an AR (anti-reflection) film. EXAMPLES

[0165] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples as long as it does not depart from the gist of the invention. In the examples, "parts" are by weight.

[0166] In the following examples, the bioplastic degree, ester group concentration, heat of crystalline fusion, weight average molecular weight, glass transition temperature, acid value of the polyester resin, the bioplastic degree of the pressure-sensitive adhesive composition, and the gel fraction of the pressure-sensitive adhesive were measured according to the methods described above.

[0167] The polyester resins (A-1) to (A-3) were produced by the following method.

[0168] [Production Example 1: Production of Polyester Resin (A-1)] In a reaction vessel equipped with a thermometer, a stirrer, a distillation column, a nitrogen inlet tube and a vacuum device, 17.0 parts (0.45 moles) of sebacic acid as polyvalent carboxylic acids (a1), 58.5 parts (0.55 moles) of hydrodistilled dimer acid (manufactured by Croda, "Pripol 1009"), 15.6 parts (1.7 moles) of ethylene glycol and 0.2 parts (0.0065 moles) of trimethylolpropane as polyol (a2), and 0.01 parts of tetrabutyl titanate as a catalyst were charged, and the internal temperature was gradually raised to 250 ° C., and an esterification reaction was carried out over 4 hours. Thereafter, the internal temperature was raised to 260 ° C., and 0.01 parts of tetrabutyl titanate was charged as a catalyst, the pressure was reduced to 1.33 hPa, and a polymerization reaction was carried out over 3 hours to produce a polyester resin (A-1). The composition and physical properties of the resulting polyester resin (A-1) are shown in Table 1 below.

[0169] [Production Example 2: Production of Polyester Resin (A-2)] In a reaction vessel equipped with a thermometer, a stirrer, a distillation column, a nitrogen inlet tube and a vacuum device, 84.3 parts (1.00 mol) of hydrodistilled dimer acid (manufactured by Croda, "Pripol 1009") as polyvalent carboxylic acids (a1), 15.6 parts (1.7 mol) of ethylene glycol and 0.1 parts (0.0065 mol) of trimethylolpropane as polyols (a2), and 0.01 parts of tetrabutyl titanate as a catalyst were charged, and the internal temperature was gradually raised to 250 ° C., and an esterification reaction was carried out over 4 hours. Thereafter, the internal temperature was raised to 260 ° C., 0.01 parts of tetrabutyl titanate was charged as a catalyst, the pressure was reduced to 1.33 hPa, and a polymerization reaction was carried out over 3 hours to produce a polyester resin (A-2). The composition and physical properties of the resulting polyester resin (A-2) are shown in Table 1 below.

[0170] [Production Example 3: Production of polyester resin (A-3)] In a reaction vessel equipped with a thermometer, a stirrer, a distillation column, a nitrogen inlet tube and a vacuum device, 49.2 parts (1.00 mol) of hydrodistilled dimer acid (manufactured by Croda, "Pripol 1009") as polyvalent carboxylic acids (a1), 50.8 parts (1.09 mol) of dimer diol (manufactured by Croda, "Pripol 2033") as polyol (a2), and 0.01 parts of tetrabutyl titanate as a catalyst were charged, and the internal temperature was gradually increased to 200 ° C., and an esterification reaction was carried out over 4 hours. Thereafter, the internal temperature was increased to 240 ° C., 0.01 parts of tetrabutyl titanate was charged as a catalyst, the pressure was reduced to 1.33 hPa, and a polymerization reaction was carried out over 3 hours to produce a polyester resin (A-3). The composition and physical properties of the resulting polyester resin (A-3) are shown in Table 1 below.

[0171] [Table 1]

[0172] Next, prior to preparing the pressure-sensitive adhesive composition, the following components were prepared.

[0173] [Carbodiimide group-containing compound (B)] Carbodiimide compound (B-1): Aromatic polycarbodiimide compound "Carbodilite V-09GB" (Nisshinbo Chemical Co., Ltd.), the terminal of which is substituted with a substituent derived from an aromatic monoisocyanate, weight average molecular weight: 6000 Carbodiimide compound (B-2): "Carbodilite V-04PF" (Nisshinbo Chemical Co., Ltd.), an aromatic polycarbodiimide compound in which the isocyanate end is substituted with a substituent derived from polyethylene glycol monomethyl ether having a molecular weight of 500, weight average molecular weight: 5300

[0174] [Crosslinking agent (C)] Aliphatic isocyanate crosslinking agent (C-1): "Coronate HX" (manufactured by Tosoh Corporation) Aromatic isocyanate crosslinking agent (C-2): "Coronate L55E" (manufactured by Tosoh Corporation) Aliphatic bifunctional isocyanate crosslinking agent (C-3): "Duranate D101" (manufactured by Asahi Kasei Corporation)

[0175] [Urethanization catalyst (D)] Zirconium compounds (D-1): "Orgatics ZC-150" (Matsumoto Fine Chemical Co., Ltd.) (diluted with acetylacetone to a solids concentration of 1%)

[0176] [Antioxidants (E)] Hindered phenol-based antioxidant (E-1): "IRGANOX1010" (manufactured by BASF)

[0177] Using the polyester resins (A-1) to (A-3) obtained above and the above-mentioned components, pressure-sensitive adhesive compositions were prepared as described below, and pressure-sensitive adhesive sheets were produced.

[0178] [Example 1] The polyester resin (A-1) obtained above was diluted with ethyl acetate to a solid content concentration of 50%, and 100 parts of the resulting solid content were mixed with 1 part (solid content) of a carbodiimide compound (B-1), 1 part (solid content) of an aliphatic isocyanate crosslinking agent (C-1), 0.05 parts (solid content) of a zirconium compound (D-1), and 0.1 parts (solid content) of a hindered phenol antioxidant (E-1), and the mixture was stirred and mixed to obtain a pressure-sensitive adhesive composition. The adhesive composition obtained above was applied onto a 38 μm-thick release film made of PET (polyethylene terephthalate) using an applicator and dried at 100° C. for 5 minutes to obtain an adhesive sheet with an adhesive layer thickness of 50 μm. The surface of the resulting pressure-sensitive adhesive layer was then covered with a 38 μm thick PET release film with a different peel strength from the release film, and aging treatment was carried out at 40° C. for 10 days to obtain a substrate-less double-sided pressure-sensitive adhesive sheet.

[0179] [Examples 2 to 7, Comparative Examples 1 to 5] A pressure-sensitive adhesive composition was prepared in the same manner as in Example 1, except that the ingredients were blended as shown in Table 2 below, and a substrate-less double-sided pressure-sensitive adhesive sheet was obtained.

[0180] [Table 2]

[0181] The following evaluations were carried out on the obtained pressure-sensitive adhesive sheets of Examples 1 to 7 and Comparative Examples 1 to 5. The evaluation results are shown in Table 3 below.

[0182] <Adhesive haze> The release film on one side of the substrate-less double-sided adhesive sheet obtained above was peeled off, and the exposed adhesive layer was bonded to an alkali-free glass plate (Corning Incorporated, Eagle XG), and then the release film on the opposite side was peeled off to produce a test specimen having the configuration adhesive layer / alkali-free glass plate. The haze of this test piece was measured using a HAZE MATER NDH2000 (manufactured by Nippon Denshoku Industries Co., Ltd.), and the haze value of the pressure-sensitive adhesive layer was determined by subtracting the haze value of the alkali-free glass plate, and the haze was evaluated according to the following criteria. The haze meter complies with JIS K7361-1.

[0183] <Mark resistance> When preparing the substrate-less double-sided pressure-sensitive adhesive sheet, a pressure-sensitive adhesive layer was formed by drying for 5 minutes at 100° C. Thereafter, a release-treated PET film (release film) was attached to the pressure-sensitive adhesive layer, and a 2 kg roller with a diameter of 7.5 cm and a width of 5 cm was placed on the release film, stopped for 10 seconds, and then the roller was removed. The pressure-sensitive adhesive layer was visually observed and evaluated according to the following criteria. (Evaluation Criteria) ○ No change. × There are dents where the roller was placed.

[0184] <Gel fraction of adhesive> [Early (G1)] The release film on one side of the substrate-less double-sided PSA sheet obtained above was peeled off, the exposed PSA layer was wrapped in a 200 mesh SUS wire netting and immersed in toluene at 23°C for 24 hours, and the weight percentage of the insoluble PSA component remaining in the wire netting after immersion relative to the weight of the PSA component before immersion was defined as the gel fraction, minus the weight of the release film. [85℃×85%RH×500 hours later (G2)] The substrate-less double-sided pressure-sensitive adhesive sheet obtained above was left to stand in a high-temperature constant-humidity chamber at a temperature of 85°C and a humidity of 85%RH for 500 hours. The release film on one side was peeled off from this substrate-less double-sided pressure-sensitive adhesive sheet, and the exposed pressure-sensitive adhesive layer was wrapped in a 200-mesh SUS wire net and immersed in toluene at 23°C for 24 hours. The weight percentage of the insoluble pressure-sensitive adhesive component remaining in the wire net after immersion relative to the weight of the pressure-sensitive adhesive component before immersion was defined as the gel fraction. However, the weight of the release film was subtracted. [Retention rate] The gel fraction (G2) after 500 hours at 85°C and 85% RH was divided by the initial gel fraction (G1) to obtain the retention rate, which was evaluated according to the following criteria. (Evaluation Criteria) 〇: Retention rate 70% or more ×: Retention rate less than 70%

[0185] [Preparation of adhesive sheet with substrate] The release film on one side of each of the substrate-less double-sided pressure-sensitive adhesive sheets obtained above was peeled off, and the pressure-sensitive adhesive layer was transferred to a PET film (38 μm) to prepare a pressure-sensitive adhesive sheet with a substrate for evaluating adhesive strength.

[0186] <Adhesive strength (peel strength) (against SUS304-BA plate)> A SUS304-BA plate was prepared as an adherend. The adhesive sheet with the substrate obtained above was cut to 25 mm x 200 mm in an environment of 23 ° C and 50% RH, and then the release film was peeled off, the adhesive layer side was abutted against the SUS304-BA plate, and a 2 kg roller was reciprocated to pressurize and attach it. Then, after leaving it for 30 minutes in the same atmosphere, the 180 degree peel strength (N / 25 mm) was measured at a peel speed of 300 mm / min using an autograph (Shimadzu Corporation, Autograph AGS-H 500N) and evaluated according to the following criteria. Note that SUS304-BA sheet refers to SUS304 that has been cold-rolled and then bright annealed (non-oxidation annealed), or that has been skin-pass rolled to enhance gloss. (Evaluation Criteria) ○...5N / 25mm or more × Less than 5N / 25mm

[0187] <Adhesive strength (peel strength) (against glass)> An alkali-free glass plate (Corning XG) was prepared as an adherend. The adhesive sheet with the substrate obtained above was cut to 25 mm x 200 mm in an environment of 23 ° C. and 50% RH, and then the release film was peeled off, the adhesive layer side was abutted against an alkali-free glass plate, and a 2 kg roller was reciprocated to pressurize and attach it. Then, after leaving it for 30 minutes in the same atmosphere, the 180 degree peel strength (N / 25 mm) was measured at a peel speed of 300 mm / min using an autograph (Shimadzu Corporation, Autograph AGS-H 500N), and evaluated according to the following criteria. (Evaluation Criteria) ○...5N / 25mm or more △ 1N / 25mm or more, less than 5N / 25mm ×...Less than 1N / 25mm

[0188] [Table 3]

[0189] From the results in Table 3, the adhesives of Examples 1 to 7 had sufficiently low haze and excellent transparency even when the adhesive layer was thick. In addition, since the adhesive layer has high restoring power, even if the adhesive layer is deformed, no trace remains and the adhesive layer has excellent resistance to dents, and further has excellent durability and adhesive power. Therefore, the adhesive is suitable for optical members and window films where the adhesive layer is visible, and is also environmentally friendly. On the other hand, the adhesives of Comparative Examples 1 to 3, which did not contain a carbodiimide group-containing compound, were poor in retention rate (durability).Also, the adhesives of Comparative Examples 3 to 5 were poor in dent resistance.Furthermore, the adhesives of Comparative Examples 4 and 5 had high haze and were not suitable for practical use. [Industrial Applicability]

[0190] The adhesive of the present invention uses environmentally friendly plant-derived raw materials, and even when a polyester-based resin and adhesive composition with a high bioplasticity is used, it has excellent durability and transparency even under high temperature and high humidity conditions, and has excellent adhesive properties for various adherends such as metals and plastics, and is suitable for use as a single-sided or double-sided adhesive sheet for bonding optical components or window films.

Claims

1. A pressure-sensitive adhesive obtained by crosslinking a pressure-sensitive adhesive composition [I] containing a polyester resin (A) having a structural portion derived from a polyvalent carboxylic acid (a1) and a structural portion derived from a polyol (a2) and a carbodiimide group-containing compound (B), The polyester-based resin (A) is a polyester-based resin containing a structural portion derived from at least one of a dimer acid and a dimer diol, the content of structural moieties derived from at least one of dimer acids and dimer diols in the polyester-based resin (A) is 50% by weight or more based on the weight of the polyester-based resin (A); the content of the carbodiimide group-containing compound (B) is 0.01 to 10 parts by weight based on 100 parts by weight of the polyester resin (A); When the pressure-sensitive adhesive is used to form a pressure-sensitive adhesive layer having a thickness of 50 μm, the haze of the pressure-sensitive adhesive layer is 5% or less, The adhesive is used to prepare an adhesive sheet with a substrate comprising an adhesive layer having a thickness of 50 μm and a polyethylene terephthalate substrate having a thickness of 38 μm, and the adhesive strength measured by the following measurement method is 5 N / 25 mm or more. [Measurement method] The adhesive sheet with the substrate is cut to 25 mm x 200 mm in an environment of 23°C and 50% RH, and then the adhesive layer side is brought into contact with a SUS304-BA plate and pressure-applied by reciprocating a 2 kg roller. After that, it is left to stand for 30 minutes in an environment of 23°C and 50% RH, and then the 180° peel strength (N / 25 mm) is measured using an autograph at a peel speed of 300 mm / min.

2. The pressure-sensitive adhesive according to claim 1, characterized in that the content of the structural moiety derived from the dimer acids is 50% by weight or more in the structural moiety derived from the polyvalent carboxylic acids (a1).

3. The pressure-sensitive adhesive according to claim 1 or 2, characterized in that the structural portion derived from the polyvalent carboxylic acids (a1) contains a structural portion derived from an aliphatic dicarboxylic acid having 4 to 16 carbon atoms.

4. The pressure-sensitive adhesive according to claim 3, characterized in that the content of the structural moiety derived from the aliphatic dicarboxylic acids having 4 to 16 carbon atoms is 10 to 80 wt % in the structural moiety derived from the polyvalent carboxylic acids (a1).

5. The pressure-sensitive adhesive according to any one of claims 1 to 4, characterized in that the content of the structural moiety derived from the dimer diol is 1 to 90 wt% in the structural moiety derived from the polyol (a2).

6. The pressure-sensitive adhesive according to any one of claims 1 to 5, characterized in that the structural moiety derived from the polyol (a2) contains a structural moiety derived from a polyol having 4 or less carbon atoms.

7. The pressure-sensitive adhesive according to any one of claims 1 to 6, characterized in that the content of structural moieties derived from a polyol having 4 or less carbon atoms is 5 to 100 wt% in the structural moieties derived from the polyol (a2).

8. The pressure-sensitive adhesive according to any one of claims 1 to 7, characterized in that the polyester resin (A) has an ester group concentration of 2 mmol / g or more.

9. The pressure-sensitive adhesive according to any one of claims 1 to 8, characterized in that the carbodiimide group-containing compound (B) has a weight average molecular weight of 1,000 or more.

10. The pressure-sensitive adhesive according to any one of claims 1 to 9, characterized in that the retention rate (G2 / G1) of the gel fraction (G2) after standing for 500 hours at 85°C and 85% RH relative to the initial gel fraction (G1) of the pressure-sensitive adhesive is 70% or more.

11. The pressure-sensitive adhesive according to any one of claims 1 to 10, characterized in that the pressure-sensitive adhesive composition [I] further contains a crosslinking agent (C).

12. The pressure-sensitive adhesive according to any one of claims 1 to 11, characterized in that the pressure-sensitive adhesive composition [I] has a bioplasticity of 60% or more.

13. An adhesive for attaching optical members or window films, comprising the adhesive according to any one of claims 1 to 12.

14. A pressure-sensitive adhesive sheet comprising a pressure-sensitive adhesive layer containing the pressure-sensitive adhesive according to any one of claims 1 to 12 or the pressure-sensitive adhesive for bonding optical members or window films according to claim 13.

15. The method for producing a pressure-sensitive adhesive sheet according to claim 14, comprising the step of coating with the pressure-sensitive adhesive composition [I] having a solvent content of 10% by weight or less.

Citation Information

Patent Citations

  • Polyester-based adhesive sheet excellent in transparency

    JP2008013593A

  • Polyester, polyester composition, adhesive composition, adhesive layer, and adhesive sheet

    JP2010037463A

  • Pressure-sensitive adhesive sheet for surface protection

    JP2011088958A

  • Adhesive composition, adhesive layer, adhesive tape, and double-sided adhesive tape

    JP2015134906A

  • Polyester adhesive composition, polyester adhesive, adhesive sheet for optical members, double-sided adhesive sheet with no substrate for optical members, optical member with adhesive layer, and optical laminate

    JP2017115149A